Il ruolo dei Cardinali nella Costituzione Apostolica Pastor Bonus sulla Curia Romana (Stato, Chiese e pluralismo confessionale, 2015)
Contributo sottoposto a valutazioneSOMMARIO: 1. Premessa – 2. I Cardinali nelle Congregazioni Romane – 3. Le “Riunioni di Cardinali” nella Curia Romana – 3.1 Il rapporto tra i Concistori e la Curia Romana – 3.2 Le Riunioni Interdicasteriali – 3.3 Il Consiglio di Cardinali per lo studio dei problemi organizzativi ed economici della Santa Sede – 4. Il Cardinale Segretario di Stato – 5. I Cardinali nei Pontifici Consigli e negli Uffici della Curia Romana – 6. I Cardinali nei Tribunali – 7. Conclusione.ABSTRACT: The role of the Cardinals in the Apostolic Constitution Pastor Bonus on the Roman CuriaThe Cardinals are the main collaborators of the Roman Pontiff in governing the universal Church. This collaboration takes place both at the collegiate level in consistories and individually within the Roman Curia. The Apostolic ConstitutionPastor Bonus promulgated in 1988 by St. John Paul II devotes ample space to the service offered by the Cardinals in the departments. The author of this article will attempt to analyze the tasks entrusted to the Cardinals in the various Dicasteri, in particular at Congregations and the Secretariat of State, and pointing out the differences with the previous discipline of Regimini Ecclesiae Universae. Special attention will be devoted to the activity of coordination curial left to the Meeting of Cardinals and finally the relationship and discipline posed by Pastor Bonus to the relationship between the Roman Curia and the Consistories.
Keywords: Diritti delle religioni